ANALISIS KINERJA KONTRAKTOR PELAKSANA PADA PEKERJAAN KONSTRUKSI REHABILITASI JALAN DANA DAK 2022 KABUPATEN MALANG - Dadang Najib (Jurnal Teknik Sipil Info Manpro, 2024)
Road is one of basic infrastructure playing crucial role in development process. Good condition of road creates properes transportation system. It, in turns ensures smooth movement of men and goods. Good transportation will make price of public goods cheap. So far, road rehabilitation works in Malang regency are conducted by usin Special Allocation Fund raising severeal problems such as late down payment, material queue and other. This study aims at analysisng performance of contractor of road rehabiitation using Special Allocation Fund of 2022 in Malang Regency. Customer Satisfaction Index analysis is used to analyse the contractors performance. In addition, Importance Performance Analysis is employed to find out performance variabel that should be improved or maintained. Then, simple linear regression analysis is used to find out the correlation between stakeholders’ level of satisfaction and performance importance on the part of contractors of road rehabilitation works using Special Allocation Fund of 2022 in Malang Regency. The findings shows that stakehoders are higly satisfied with performance of contractors of road rehabilitation works using Special Allocation Fund of 2022 in Malang Regency. It is shown by score of CSI 86,99%. It is also found that there is positive and significant correlation between stakeholders’ level of satisfaction and performance importance on the part of contractors of road rehabilitation works using Special Allocation Fund of 2022 in Malang Regency. However, there are some performance variables that should be improved by the contractors.